Legal Aspects of Crypto Assets on Indonesian Digital Investment Development - Kusnadi, Egi Hadi; Nasir, Rifqi Ridlwan; Hulwanullah, Hikam (UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to understand the legal aspect of digital investment in Indonesian crypto assets which is linked to the theories of legal certainty, justice, and benefit. Currently, Indonesian people are very fond of the cryptocurrency digital investment trend. The Indonesian government has provided several regulations regarding the physical crypto market mechanism. However, the rules regarding cryptocurrencies cannot guarantee that problems will not arise in the future. Moreover, cryptocurrency and its rules are still very new. There is still a lot of confusion in society about whether crypto investment is safe or not. This study is normative juridical study using a statutory and conceptual approach, which is summarized by examining statutory regulations and related legal doctrine. The results of this study explain that the Indonesian government is opening up opportunities by legalizing digital crypto investment activities to strengthen the economic sector. Crypto in Indonesia can only be used as an investment instrument, not currency. The implementation of crypto asset trading is regulated in the Commodity Futures Trading Supervisory Agency (Bappebti) Regulation Number 5 of 2019 concerning Technical Provisions for the Implementation of Physical Crypto Asset Markets. This regulation regulates the use of Good Corporate Governance principles in the context of carrying out buying and selling of crypto assets on the Crypto Futures Exchange (CFX). Bappebti's regulations were then changed with the enactment of Law Number 4 of 2023 concerning Development and Strengthening of the Financial Sector (UU P2SK) which expanded the authority and responsibility of the Financial Services Authority (OJK) to include digital financial assets, crypto assets and Financial Technological Innovation Sector. (ITSK).